Induction chemotherapy and hepatic artery embolization followed by extended resection for locally advanced gallbladder cancer: a case report - Chisato Takagi; Michio Sato; Masato Tomita; Atsushi Sugita; Toshiki Tokuda; Koki Fujiwara; Nobutoshi Ando (Surgical Case Reports)
Abstract Background Surgical resection plays a critical role in the curative therapy of patients with gallbladder cancer. However, extended resection for locally advanced gallbladder cancer is a controversial procedure because of the high operative morbidity, mortality, and poor prognosis after surgery, without consensus of its suitability. Several reports have described preoperative treatment modalities to reduce the risk of mortality and morbidity and improve the curability of surgery for locally advanced GBCA. However, only a few well-designed studies have verified the benefits of these preoperative strategies. Case presentation A 62-year-old male patient presented to our department with a gallbladder tumor detected on abdominal ultrasound during an annual medical checkup. Multi-phase enhanced CT revealed a gallbladder tumor with a maximum diameter of 34 mm, invading the right hepatic artery, pancreatic head, hepatic flexure of the colon, and first portion of the duodenum. We diagnosed gallbladder carcinoma as cT4 cN0 cM0 cStage IVA in the Union for International Cancer Control (UICC) classification 8th edition. After administration of 12 cycles of gemcitabine and cisplatin plus S-1 regimen, tumor shrinkage was observed on computed tomography, and elevated serum CA19-9 levels were reduced to normal limits. After preoperative hepatic artery embolization, we performed gallbladder bed resection with pancreaticoduodenectomy (minor hepatopancreatoduodenectomy) and combined resection of the right hepatic artery and hepatic flexure of the colon. Histological examination revealed no evidence of lymph node metastasis (ypT4 ypN0 ycM0 yp Stage IVA in the 8th edition of the UICC). The proximal bile duct and dissected margins were negative. Conclusions The combination of induction chemotherapy and preoperative hepatic artery embolization, followed by minor hepatopancreatoduodenectomy and combined resection of the involved arteries and partial colon, could be a feasible treatment strategy for patients with locally advanced gallbladder cancer invading neighboring organs.